Controlled drug release from hydrogels for contact lenses: drug partitioning and diffusion - Pimenta, A.F.R. (2016)
Optimization of drug delivery from drug loaded contact lenses assumes understanding the drug transport mechanisms through hydrogels which relies on the knowledge of drug partition and diffusion coefficients. We chose, as model systems, two materials used in contact lens, a poly-hydroxyethylmethacrylate (pHEMA) based hydrogel and a silicone based hydrogel, and three drugs with different sizes and charges: chlorhexidine, levofloxacin and diclofenac. Equilibrium partition coefficients were determined at different ionic strength and pH, using water (pH 5.6) and PBS (pH 7.4). The measured partition coefficients were related with the polymer volume fraction in the hydrogel, through the introduction of an enhancement factor following the approach developed by the group of C. J. Radke (Kotsmar et al., 2012; Liu et al., 2013). This factor may be decomposed in the product of three other factors EHS, Eel and Ead which account for, respectively, hard-sphere size exclusion, electrostatic interactions, and specific solute adsorption. While EHS and Eel are close to 1, Ead > > 1 in all cases suggesting strong specific interactions between the drugs and the hydrogels. Adsorption was maximal for chlorhexidine on the silicone based hydrogel, in water, due to strong hydrogen bonding. The effective diffusion coefficients, De, were determined from the drug release profiles. Estimations of diffusion coefficients of the non-adsorbed solutes D = De × Ead allowed comparison with theories for solute diffusion in the absence of specific interaction with the polymeric membrane.